ELECTRONIC MONEY AND DIGITAL CURRENCIES: A COMPARATIVE STUDY OF THEIR LEGAL NATURE - Rafad Ali Hussein (PT. Antis International Publisher, 2026)
Objective: The purpose of the current research is to explore the concepts of electronic money and digital currencies and make an analysis of their characteristics and legal nature through comparing them taking into consideration the fast evolution of the digital financial market. The relevance of the research lies in the wide-spread use of digital means of payments and legal problems that arise from the necessity of regulation and protection of users. Method: An analytical and comparative method has been used in the process of the research. Legal acts, jurisprudence and legislation regarding electronic money and digital currencies have been studied. Results: The show that the concept of electronic money is connected with the traditional fiat currency, which is issued by the licensed financial institutions and regulated by the monetary authorities. On the other hand, digital currencies, especially cryptocurrencies, are characterized by their decentralization and not always the control of a particular official authority. The research shows that electronic money and digital currencies have some similar economic features and use digital technologies for their transactions. However, there are certain differences in the issues of issuance, regulation, and legal protection. Novelty: As a conclusion, it can be stated that there is a necessity for development of special legal framework for regulation of electronic money and digital currencies.